Selective Dissolution-Derived Nanoporous Design of Impurity-Free Bi2Te3 Alloys with High Thermoelectric Performance - Lee, seung hyeok; Jung, Sung jin; Park, Gwang Min; Minyoung Na; Kim, Kwang-Chon; Hong Junpyo; Lee, Albert S. S.; BAEK, SEUNG HYUB; Kim, Heesuk; Park, Tae Joo; Kim, Jin-Sang; Kim, Seong Keun (Wiley - V C H Verlag GmbbH & Co., 2023)
Thermoelectric technology, which has been receiving attention as a sustainable energy source, has limited applications because of its relatively low conversion efficiency. To broaden their application scope, thermoelectric materials require a high dimensionless figure of merit (ZT). Porous structuring of a thermoelectric material is a promising approach to enhance ZT by reducing its thermal conductivity. However, nanopores do not form in thermoelectric materials in a straightforward manner; impurities are also likely to be present in thermoelectric materials. Here, a simple but effective way to synthesize impurity-free nanoporous Bi0.4Sb1.6Te3 via the use of nanoporous raw powder, which is scalably formed by the selective dissolution of KCl after collision between Bi0.4Sb1.6Te3 and KCl powders, is proposed. This approach creates abundant nanopores, which effectively scatter phonons, thereby reducing the lattice thermal conductivity by 33% from 0.55 to 0.37 W m(-1) K-1. Benefitting from the optimized porous structure, porous Bi0.4Sb1.6Te3 achieves a high ZT of 1.41 in the temperature range of 333-373 K, and an excellent average ZT of 1.34 over a wide temperature range of 298-473 K. This study provides a facile and scalable method for developing high thermoelectric performance Bi2Te3-based alloys that can be further applied to other thermoelectric materials.